Factors affecting the prolongation of mechanical ventilation in patients after cardiac surgery - Mahdieh Sharifzadeh Kermani; Tania Dehesh; Shiva Pouradeli; Bahareh Soltani Esmaili (Journal of Cardiothoracic Surgery)
Abstract Background This study aimed to investigate the major predictive factors associated with prolonged mechanical ventilation(PMV) following cardiac surgery. Methods This retrospective, cross-sectional, descriptive-analytical study was conducted from September 2021 to March 2022, involving 244 patients who underwent cardiac surgery. PMV was defined as mechanical ventilation for more than 24 h. Potential risk factors before, during, and after surgery were examined and recorded. Logistic regression analysis was performed to assess the relationship between demographic, clinical variables, and prolonged mechanical ventilation. A significance level of 0.05 was used for data analysis. Results The study population consisted of 68.4% male and 31.6% female patients, with 86.9% undergoing CABG surgery. PMV was observed in 13.1% of the patients. The findings revealed that the incidence of postoperative pneumonia increased the likelihood of PMV by more than 7 times [OR = 7.24, 95% CI=(5.12,8.14), P-value = 0.001]. Similarly, respiratory failure was associated with a 7.5-fold increase in the odds of PMV [OR = 7.56, 95% CI=(4.48,8.77), P-value = 0.042]. Drainage of one liter of blood on the first postoperative day increased the risk of PMV by 2.2 times [OR = 2.21, 95% CI=(1.98,2.46), P-value = 0.032], and the use of epinephrine was associated with a 2.73-fold increase in the odds [OR = 2.73, 95% CI=(2.24,3.11), P-value = 0.022]. Risk of PMV in the patients who had cardiac dysfunctin increased by more than 2 times.[OR = 2.58, 95%; CI = (1.33.2.87); P-value = 0.042]. In the patients need an Intra Aortic Balloon Pump(IABP) risk of PMV increased by more than 2 times. (OR = 2.74,95%,CI = 1.36,5.47: Pvalue = 0.03). The risk of PMV in the patients who had cerebrovascular accident(CVA) increased by more than three times [OR = 3.75, 95% CI = 1.26,4.84; P-value = 0.044]. For each unit increase in Euro Score 2 the chance of PMV increased by 1.38 TIMES. Furthermore ICU Mortality had a significant relationship with PMV.(Pvalue < 0.001). Conclusion The study identified postoperative complications, such as pneumonia, respiratory failure, high drainage, need to an IABP, higher EURO Score 2, Cardiac dysfunction, CVA and the use of epinephrine, as independent risk factors for PMV following cardiac surgery.